The Influence of Training, Compensation, and Work Motivation on The Performance of Provincial Legislatives Council Members in Banjarmasin - Sri Nurnaningsih; Devi Rusvitawati (PT. Hanken Sukses Jaya, 2023)
The Provincial Legislative Council in Banjarmasin is constantly considering methods to enhance the public sector. High job performance from members of the Provincial Legislative Council in Banjarmasin is required for improvement. Training, compensation, and work motivation all impact job performance. The study examined how training, compensation, and work motivation affect job performance. This study employed a quantitative approach. For this study, 45 members of the Provincial Legislative Council in Banjarmasin were sampled. The method for collecting data used was a questionnaire. The data was analyzed by Multiple Linier Regression (MLR) analysis. The findings of this study indicated that job performance, compensation, work motivation, and training all achieved satisfactory levels. The effects of training, compensation, and work motivation on job performance were all significant. The training variable substantially influenced job performance more than the other variables. Nevertheless, those factors affected the results. Because these factors had a significant influence on performance, training, compensation, and work motivation all needed to get improved.